Characteristics of patients with cervical cancer during pregnancy: a multicenter matched cohort study. An initiative from the International Network on Cancer, Infertility and Pregnancy. Issue 4 (20th March 2019) - Halaska, Michael J; Uzan, Catherine; Han, Sileny N; Fruscio, Robert; Dahl Steffensen, Karina; Van Calster, Ben; Stankusova, Hana; Marchette, Martina Delle; Mephon, Astrid; Rouzier, Roman; Witteveen, Petronella O; Vergani, Patrizia; et al.
Abstract : Background: Treatment of cervical cancer during pregnancy is often complex and challenging. This study aimed to analyze current patterns of practice in the management of pregnant patients diagnosed with cervical cancer. Methods: This was a matched cohort study comprising patients managed for cervical cancer during pregnancy from six European centers. Patient information was retrieved from the dataset of the International Network for Cancer, Infertility and Pregnancy from 1990 to 2012. Each center matched its patients with two non-pregnant controls for age (±5 years) and International Federation of Gynecology and Obstetrics (FIGO) 2009 stage. Information on age, histological type, grade, lymphovascular space invasion, stage, tumor size, method of diagnosis, site of recurrence, delivery, date of recurrence, and date of death was recorded. Progression-free survival was compared using multivariable Cox proportional hazards regression. Results: A total of 132 pregnant patients and 256 controls were analyzed. The pregnant patients (median age 34 years, range 21–43) were diagnosed at a median gestational age of 18.4 weeks of pregnancy (range 7–39). Stage distribution during pregnancy was 14.4% for stage IA, 47.0% for IB1, 18.9% for IB2, and 19.7% for II-IV. For treatment during pregnancy, 17.4% of the patients underwent surgery, 16.7% received neoadjuvant chemotherapy, 26.5% delayed their treatment, 12.9% had a premature delivery, and 26.5% had their pregnancy terminated. Median follow-up was 84 months (67 months for pregnant and 95 months for non-pregnant patients). The unadjusted hazard ratio of pregnancy for progression-free survival was 1.18 (95% confidence interval 0.74 to 1.88). Conclusion: Surgery and chemotherapy is increasingly used in the management of pregnant patients with cervical cancer and prognosis is similar to that of non-pregnant patients.